Financial Analysis of Coconut Sugar Production: A Case Study in Mempawah Regency, Indonesia - Ekawati Ekawati; Rahmatullah Rizieq; Ellyta Ellyta (Universitas Sebelas Maret, 2022)
Coconut is one of the key plantation commodities in the Mempawah Regency that needs to be developed. This is necessary in order to increase the income of coconut sugar craftsmen and also allow them gain knowledge of the industrial scale through feasibility studies on the agro-industry. Therefore, this study aims to analyze the structure of production cost and operating income as well as the feasibility of the coconut sugar agro-industry. This analysis is important for craftsmen in the regency that engage in the continuous production of coconut sugar. Furthermore, this study was conducted in Mempawah Regency with 34 coconut farmers. The analysis of the R/C ratio and Break-Even Point (BEP) was used to determine the indicator of financial feasibility. The result revealed that the average production cost needed by the agro-industry was 7,659,868 IDR month-1 and the generated income was 3,483,132 IDR month-1. Additionally, the coconut sugar agro-industry was financially feasible as the obtained R/C ratio was 1.45. The BEP of production volume and Cost of Good Solds (COGS) was 346 kg and 9,814.92 IDR which is less than the actual production volume and price. It was suggested that craftsmen of coconut sugar produce more than 346 kg of sugar per month with a selling price above 9,814.92 IDR kg-1 in order to obtain profit.